Effect of Sintering and Heat Treatment Conditions on Mechanical Properties of Martensitic Stainless Steel Fabricated by MIM Process - KYOGOKU, Hideki; NAKAYAMA, Hideki (TRANSACTIONS OF THE JAPAN SOCIETY OF MECHANICAL ENGINEERS Series A, 2011)
The effects of sintering and heat treatment conditions on the mechanical properties of martensitic stainless steel fabricated by MIM process were investigated. The specimens were made by injecting the mixture of gas-atomized powders of 5 μm and 10 μm in mean particle diameter and a polymer binder into a metallic mold. The injection molded compacts were debound in air at 593 K for 7.2 ks. They were sintered in vacuum at temperatures between 1273 K and 1623 K for 7.2 ks. And the specimens were aged at various temperatures between 373 K and 873 K after vacuum hardening. The density of the as-sintered compact of 5 μm powder was higher than that of the as-sintered compact of 10 μm powder. In case of the as-sintered compact of 5 μm powder, the tensile strength corresponded to the change in density well, and the tensile strength of the compact sintered at 1373 K was 1600 MPa. On the other hand, in the case of the as-sintered compact of 10 μm powder, the tensile strength was rather lower than that of the as-sintered compact of 5 μm powder because of coarsening of the grain size. The tensile strength and elongation of the heat-treated compact of 5 μm powder were 1800 MPa and 12 %, respectively. The tensile strength and elongation of the heat-treated compact of 10 μm powder were 1680 MPa and 10 %, respectively. Thus, the mechanical properties of the compacts were approximately equal to those of the wrought material.